Nidoviruses associated with aquatic animals - L. P. Buchatsky; V. V. Makarov (Ветеринария сегодня)
Nidoviruses comprise the most complex grouping among other viruses with respect to their multiplicity, phylogeny, systematics, species identification, genetic relationships within a taxon, progressive variability. Like other single-stranded RNA viruses, nidoviruses have a relatively high ability to mutate and recombine, which allows them to quickly adapt to new hosts and new ecological niches. Although most of the known representatives of nidoviruses are associated with terrestrial hosts, more and more data has recently appeared on nidoviruses recovered from aquatic organisms. This review is the analysis of current data on the representatives of the order Nidovirales associated with aquatic animals. They are all included in the eight families based on the current classification of viruses. The most studied among them are members of the families Coronaviridae, Tobaniviridae and Roniviridae. Representatives of the other families of aquatic animal nidoviruses were identified using metagenomic deep sequencing (metagenomics), but their effect on the host organism has not yet been adequately studied. Data on the distribution of nidoviruses among aquatic animals in different global aquatic systems are presented, clinical signs of the disease are described, a brief description of nidoviruses and their genomes is given. Nidoviruses of aquatic animals as the earliest members of the animal kingdom are supposed to have played a possible role in the evolution of terrestrial animal nidoviruses. Therefore, aquatic animal nidoviruses could play a significant role in the formation of new natural reservoirs unknown to science, as well as in their interspecies transfer between marine, freshwater and terrestrial hosts.